Interlace polynomials of friendship graphs - Christina Eubanks-Turner; Aihua Li (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2018)
In this paper, we study the interlace polynomials of friendship graphs, that is, graphs that satisfy the Friendship Theorem given by Erdös, Rényi and Sos. Explicit formulas, special values and behavior of coefficients of these polynomials are provided. We also give the interlace polynomials of other similar graphs, such as, the butterfly graph.